Pengungkapan Sustainability Reporting terhadap Kinerja Perusahaan - Aning Fitriana (Universitas Nusantara PGRI Kediri, 2024)
This research aims to obtain empirically prove the effect of sustainability reporting based on three aspects, namely economic performance (EC), environmental performance (EN), social performance (SO) on financial performance. Descriptive quantitative was chosen as the method in this research. The population of this study manufacturing companies are listed on the Indonesia Stock Exchange. The research sample used purposive sampling for 3 years in the period 2020-2022 so there were 45 companies. The data of analysis technique was multiple regression analysis. The results of this reseach simultaneously for economic performance variables, environmental performance, social performance have no effect toward financial performance. The same result for the partial test for economic performance variables, environmental performance has no effect toward financial performance.